Penerapan Metode Numbered Heads Together (NHT) untuk Meningkatkan Hasil Belajar Kognitif IPA di SD Kristen Gunungsitoli Utara [The Implementation of the Numbered Heads Together (NHT) Strategy to Increase Cognitive Achievement of Grade IV Students in a Science Class Learning about Plants at a Christian Primary School in Gunung Sitoli Utara] - Ayunda Putri Putranti; Widiastuti - (Universitas Pelita Harapan, 2016)
Science learning in grade IV requires students to be able explain the structure and function of plants. Students who could not explain the structure and the function of plants had low cognitive learning scores. The researcher used the Numbered Heads Together (NHT) strategy to increase the students’ cognitive learning score and also to discover the steps involved in applying NHT in a science class learning about plants structures. The research method used was Classroom Action Research model by Kemmis and Taggart for 2 cycles. The research was conducted at SD Kristen Gunungsitoli Utara grade IV on 26 October 2016. The instruments that were used were test sheets, students’ questionnaire sheets, researcher checklist sheets, mentor’s observation sheets, mentor’s interview sheets, students’ interview sheets, mentor’s feedback sheets, and the researcher's reflective journal. The result from this research showed that the NHT method could increase the students’ cognitive learning score when students were divided into groups, given questions, thought together, and answered the given questions. It could be concluded that the Numbered Heads Together strategy is the right method to increase cognitive learning scores. BAHASA INDONESIA ABSTRAK: Pembelajaran IPA kelas IV menuntut siswa untuk mampu menjelaskan struktur dan fungsi tumbuhan. Namun realitanya siswa belum mampu menjelaskan struktur dan fungsi tumbuhan dengan tepat sehingga menyebabkan perolehan hasil belajar kognitif siswa menjadi rendah. Peneliti menggunakan metode Numbered Heads Together (NHT) untuk mengatasi masalah tersebut. Penelitian ini bertujuan untuk meningkatkan hasil belajar kognitif siswa melalui metode NHT dan juga untuk mengetahui langkah penerapan metode NHT pada pembelajaran IPA materi bagian tumbuhan. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) model Kemmis dan Taggart selama dua siklus. Penelitian dilaksanakan di SD Kristen Gunungsitoli Utara kelas IV tanggal 26 Oktober 2016 sampai 29 Oktober 2016. Instrumen yang digunakan selama siklus antara lain lembar tes, lembar angket siswa, lembar check-list peneliti, lembar observasi guru pamong, lembar wawancara guru pamong, lembar wawancara siswa, lembar feedback guru pamong, dan jurnal refleksi peneliti. Hasil dari penelitian ini menunjukkan bahwa metode NHT dapat meningkatkan hasil belajar kognitif siswa kelas IV pada mata pelajaran IPA materi bagian tumbuhan dengan cara melakukan pembagian kelompok, memberikan pertanyaan, berpikir bersama dan menjawab pertanyaan yang diberikan. Maka dapat disimpulkan bahwa metode Numbered Heads Together merupakan metode yang tepat untuk meningkatkan hasil belajar kognitif.